2014
DOI: 10.1136/bmjopen-2013-004647
|View full text |Cite
|
Sign up to set email alerts
|

Preventive zinc supplementation for children, and the effect of additional iron: a systematic review and meta-analysis

Abstract: ObjectiveZinc deficiency is widespread, and preventive supplementation may have benefits in young children. Effects for children over 5 years of age, and effects when coadministered with other micronutrients are uncertain. These are obstacles to scale-up. This review seeks to determine if preventive supplementation reduces mortality and morbidity for children aged 6 months to 12 years.DesignSystematic review conducted with the Cochrane Developmental, Psychosocial and Learning Problems Group. Two reviewers inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 27 publications
(29 reference statements)
4
40
0
5
Order By: Relevance
“…An analysis of mostly high-quality studies has demonstrated that the risk of RTI or pneumonia and diarrhea or dysentery may be reduced in children after zinc administration [207]. However, analysis of low-to-moderate quality studies found no protective effect of zinc (5 to ≥20 mg/day) against the risk of RTI or malaria in children, although there was a reduction in mortality associated with RTI, diarrhea, and malaria; the addition of iron to zinc conferred no additional benefits [208,209].…”
Section: Micronutrients In Reducing the Risk Of Acute Infectionsmentioning
confidence: 99%
“…An analysis of mostly high-quality studies has demonstrated that the risk of RTI or pneumonia and diarrhea or dysentery may be reduced in children after zinc administration [207]. However, analysis of low-to-moderate quality studies found no protective effect of zinc (5 to ≥20 mg/day) against the risk of RTI or malaria in children, although there was a reduction in mortality associated with RTI, diarrhea, and malaria; the addition of iron to zinc conferred no additional benefits [208,209].…”
Section: Micronutrients In Reducing the Risk Of Acute Infectionsmentioning
confidence: 99%
“…Iron and zinc play a role in the immune system. (23) The immune responses by T lymphocytes will be disturbed upon a decrease in the production of cells, which is caused by decreased DNA synthesis, so that iron and zinc deficiencies may cause disorders of the immune system. (26) Children with disorders of the immune system are more susceptible to infectious disease, thus affecting nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…(22) Underfives with iron deficiency are more suceptible to microorganisms, because iron deficiency is closely associated with damaged functional capacity of the immune defense mechanism that is important for the entry of infectious disease. (23) Iron plays a role in the immune system. The immune responses by the T lymphocytes will be disturbed upon decreased production of cells, which is caused by decreased DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…absorbed iron fraction) (21)(22)(23)(24) . Meta-analysis of trials involving nearly 10 000 young children in developing countries have consistently shown that conventional soluble oral iron supplementation used to treat IDA is associated with increased infection including bloody diarrhoea (22,(25)(26)(27) and detrimental changes to the gut microbiome and gut inflammation (27,28) , further increasing the burden from enteric infection and environmental enteropathy (i.e. persistent gut damage and inflammation that leads to malabsorption), which is a major cause of growth failure in children in resource-poor environments (29,30) .…”
Section: Strategies To Prevent and Treat Iron Deficiencymentioning
confidence: 99%